Covid-19, Mengembalikan Wanita kepada Fitrah-Nya - Nova Primadina (PROCEEDING UMSURABAYA, 2020)
AbstractThe COVID-19 pandemic (Corona Virus Infection Disease 2019), which began in December2019, started in the city of Wuhan in China, has spread throughout the world, includingIndonesia. Various policies in all sectors have been changed to reduce the rate of increase inCovid-19 sufferers, but they have not shown satisfactory results with the increasing number ofCOVID-19 sufferers and have actually put the economy on the brink of recession. One of themis the Work From Home (WFH) and School From Home (SFH) policies. However, if we lookat the positive side, this policy restores the natural function of a woman to become a basicschool for her family, because by being at home, even career mothers will be able to controland handle their children directly without having to entrust them to school teachers andhousehold assistants, so that the relationship between mother and child will be betterintertwined and play an important role in the process of forming moral intelligence andcharacter building in childrenKeywords: COVID-19, parenting, mother and child